The Game: Easier or Tougher? A Study of Hamilton Millennials and Self-Employment - Martin, Jeffrey C. (Poverty and Employment Precarity in Southern Ontario/McMaster University, Labour Studies, 2016)
The effects of neoliberal capitalism have had a significant impact on the structure of the Canadian labour market and economy, but also on the employment opportunities for young workers in the early 21st century. And despite being the most educated generation ever, the millennials are faced with fewer full-time, secure jobs. Many have opted to embrace self-employment, sometimes not by choice but by necessity. This qualitative study embraced similar themes from the McMaster University/United Way of Toronto/PEPSO study, “The Precarity Penalty,” to determine how self employment affects their personal, work, social and community lives. One-on-one interviews were conducted with 10 Hamilton millennials (born 1981-1997), who were recruited through the Hamilton Chamber of Commerce’s affiliated organizations, Hamilton HIVE and Young Entrepreneurs and Professionals Hamilton. A total of 28 questions explored five topical areas: 1) their employment relationship; 2) how their employment relationship affected their life outside of work – i.e., family life, friends, community involvement; 3) physical and mental health; 4) their outlook on the future in terms of employment-related opportunities and potential barriers; and 5) their overall view on work and the current generation of workers. This research provided a glimpseinto the challenges that young, well-educated, self-employed millennials face, and their views on work and the labour market today. and their views on work and the labour market today. –From Executive Summary